Selective expression of S100A7 in lung squamous cell carcinomas and large cell carcinomas but not in adenocarcinomas and small cell carcinomas. Issue 4 (25th March 2008) - Zhang, H; Zhao, Q; Chen, Y; Wang, Y; Gao, S; Mao, Y; Li, M; Peng, A; He, D; Xiao, X
Abstract : Background: S100A7 is a secreted protein and its overexpression has been previously associated with carcinogenesis of certain cancers. This study was undertaken to investigate the possibility that overexpression of S100A7 protein might be detected in the sera of patients with lung cancer. Methods: RNA and protein levels of S100A7 were examined in 60 pairs of frozen lung cancer tissues by RT-PCR and western blot. The specific expression of this protein and its cellular distribution were investigated in 145 paraffin embedded lung cancer samples, six benign lung disease and 21 normal lung tissues by immunohistochemistry. The S100A7 protein level was further analysed in serum from 112 patients with lung cancer, 20 with benign lung diseases and 31 healthy individuals by ELISA. Results: Specific expression of both S100A7 mRNA and protein was found in squamous cell carcinomas, adenosquamous carcinomas and large cell lung carcinomas, whereas neither was detected in adenocarcinomas or paired non-cancerous lung tissues. Further immunohistochemical analysis identified positive staining of S100A7 only in squamous cell carcinomas and large cell lung carcinomas, but not in other subtypes of lung cancer and normal lung tissues. Weak expression was also found in the inflammatory cells of benign lung diseases. Our most important finding is that elevated S100A7 protein could be detected in the sera of patients with squamous cell carcinomas. Conclusion: S100A7 was only expressed in squamous cell carcinomas and large cell lung carcinomas and an increase in the level of S100A7 protein in serum may serve as a potential marker for lung cancer diagnosis.